ANALISIS SIFAT FISIK TANAH PADA AREAL BEKAS TEBANGAN HUTAN TANAMAN INDUSTRI (HTI) KABUPATEN GORONTALO UTARA PROVINSI GORONTALO - Puspaningrum, Dian; Djabar, Murni (Universitas Gorontalo, 2018)
The ground as a system that dynamic, the ground can be turned off than time to tim , according its properties which includes the physical properties , the chemical nature and the nature of mechanical, as well as the state of the environment that productivity a whole determine the ground .A pattern of land use affect the trait of land especially the physical properties of a soil , because the use of or cultivation of the land can result in a system of capillaries on the dotted the ground and the breakdown of the limits of the horizon the ground which gives rise to a setback the physical properties of soil and chemical , as forfeited to the element of the disturbances and organic matter . The opening of the woodland plant industry ( HTI ) indirectly affect the physical properties on the ground .Reason this is research objectives , which is to know the true nature of the physical land in the land clearing areal woodland plant industry (HTI). This research is divided into two (2) , activities in the field of the sample collection and testing the sample in the laboratory .The sample collection in the field in a purposive sampling .While the sample done in a laboratory to determine soil texture ,the permeability, the heavy volume ,a color of soil ,the stability of a structure.The result showed that a color of soil the area of land clearing dominated by the orange color criteria class texture clay , to be the area of natural forest dominated by a shade of brown with class criteria soil texture loam clays , and to the acreage the planting of crops jabon the age of 4 years is dominated by a shade of brown with class criteria soil texture loam clays .Permeability class each area ranged ranging from class criteria rather slow until with the class rather fast.